Activity and electrochemical stability of a chromium modified nickel catalyst for oxygen reduction reaction. (10th May 2017) - Kondov, Ivan; Faubert, Patrick; Müller, Claas
Abstract: Effective catalysts for electrochemical oxygen reduction reaction should have both high activity and stability under relevant electrochemical conditions of fuel cells. For sustainable and scalable applications it is important to identify catalyst material candidates that are free of precious metals or rare elements. We combine modeling based on density functional theory and experimental characterization to study a nickel based catalyst modified with Cr. To describe the catalytic activity within the model, we computed the O and OH adsorbate binding energies, the effective reversible potential and the critical potential for the oxygen reduction reaction. The stability of different overlayer structures has been analyzed by means of surface Pourbaix diagrams which show that the decorating Cr atoms considerably stabilize the catalyst surface against dissolution for large ranges of potentials and pH. Both the measured voltammograms and the analysis of the simulated structures indicate increased catalytic activity of the Cr modified catalyst.